MUTAGENIC AND MODIFYING EFFECTS OF NEW BIOACTIVE SUBSTANCES FOR MAMMALS - Strygelchyk, N.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The potential mutagenic and modifying effect of bioactive substances derived from human amniotic tissue and possessing anti-inflammatory and healing effects have been investigated mammals. It was shown that the injection of the stud substances in doses that were 100 times higher than daily ones did not induce the rise of chromosomal aberration frequlcy in bone marrow cells, and of dominant lethal mutations in mouse gametes. The obtained results have been discussed in terms of possible usage of the studied substances in the medical practice.